UNIFIKASI THIBBUN NABAWI REBUSAN SIRIH HIJAU PADA IBU PASCA SALIN DENGAN ROBEKAN PERINEUM DI PKD SRI REJEKI PLUPUH SRAGEN - Yuliaswati, Enny (P3M STIKES Aisyiyah Surakarta, 2020)
Background: Lack of cleanliness in the genetal area is a problem that is commonly found in post-saline mothers especially with perineal tears. Care for the genetal area of the puerperal mother is important because it can prevent odor and accelerate the healing of the perineum. The presence of injuries to body tissues is very risky of infection. The potential for infection in the perineum because the perineum in the puerperal mother is a moist area. Nursing perineal sutures using green betel stew is effective to speed up the drying of the stitches. Purpose: Community service is to increase knowledge about perineal suture care using green betel stew. Method: This service was carried out for one month in the form of health promotion through home visits to perform perineal care with seams with green betel stew. interactive discussion with material about how to early detect cervical cancer. Results: Based on observations during community service activities, several positive results were obtained, such as: 1). Postpartum mothers with perineal sutures consisting of 12 postpartum mothers. 2). Community service participants gave positive responses. 3) The healing period of perineal suture occurs within 4-5 days. The conclusion of this activity is health promotion with home visits can increase knowledge about how to care for perineal sutures. Keywords: perineum rupture; green betel stew; health promotion